HUBUNGAN SIKAP KERJA BERDIRI, KARAKTERISTIK PEKERJA, DAN PENGGUNAAN HIGH HEELS TERHADAP TINGKAT KELELAHAN KERJA PADA SALES PROMOTION GIRL (SPG) DI SWALAYAN KOTA SEMARANG - Maharani, Aisya Mauliana; Wahyuni, Ida; Widjasena, Baju (Jurnal Kesehatan Masyarakat (Undip), 2021)
This study aims to determine whether there is a relationship among standing work attitude, worker characteristics, and the use of high heels on work fatigue experienced by Sales Promotion Girl (SPG) in Semarang City Supermarkets. The background of the research is that a SPG who works with a standing work position and wears high heels will experience an incidence of work fatigue. This is quantitative research with a cross-sectional study approach. The instruments in this study were the IFRC questionnaire, ruler, microtoise, body scale, and REBA Method Sheet. The population in this research consists of 150 people. The research employed an incidental sampling with a total sample of 38 people. Data analysis in this research made use of the Spearman rank correlation test. The findings of the research showed that among the 38 Sales Promotion Girls (SPG) who had a standing work position;  16 people were with low risk and 22 people were very low. Based on their ages, 9 people were 30 years old and 29 people were below 30 years old. As with their service time category, as many as 24 people had a long time experience and 14 people were with short period of service time. The results of the statistical test showed that there is a significant correlation between standing work position, wearing of high heels with work fatigue. In addition, there is no significant correlation between worker characteristics (Age, Work Period, Body Mass Index) and work fatigue on SPG at Supermarkets in Semarang City.